Stories and ballads of the far past - Chadwick, Nora K. (Nora Kershaw), 1891-1972. (Cambridge : University Press, 1921)
"List of editions and translations": p. [254]-256. Part I. Sagas: The tháttr of Nornagest. The tháttr of Sörli. The saga of Hromund Greipsson. The saga of Hervör and Heithrek. Appendix: The combat at Samsø and Hjalmar's death song.--Part II. Ballads: Gríplur I. The Faroes ballad of Nornagest. The Faroese ballad of Hjalmar and Angantyr. The Danish ballad of Angelfyr and Helmer. The Faroese ballad of Arngrim's sons. The Faroese riddle ballad (Gátu Ríma). The Shetland ballad of Hildina. Mode of access: Internet.